The integrated model for solving the single-period deterministic inventory routing problem - Abdul Rahim, Mohd Kamarul Irwan (2016)
This paper discusses the problem of efficiently managing inventory and routing problems in a two-level supply chain system.Vendor Managed Inventory (VMI) policy is an integrating decisions between a supplier and his customers.We assumed that the demand at each customer is stationary and the warehouse is implementing a VMI.The objective of this paper is to minimize the inventory and the transportation costs of the customers for a two-level supply chain.The problem is to determine the delivery quantities, delivery times and routes to the customers for the single-period deterministic inventory routing problem (SP-DIRP) system. As a result, a linear mixed-integer program is developed for the solutions of the SP-DIRP problem.